Hubungan perilaku pencarian informasi guru militer dengan hasil pembelajaran pembekalan angkutan TNI AD Cimahi - Purnama, Sita; Yusup, Pawit M.; Kurniasih, Nuning (Jurnal Kajian Informasi dan Perpustakaan, 2017)
Information needs are necessary for humans to answer questions that are in the mind, in order to enhance their professions or main activities. The needs of each person are influenced by different situations, cognitions and physiological backgrounds. All aspects of human life require information which is expected to continuously support the improvement of life patterns toward increasing complexities. The purpose of this study was to identify and analyze the relationship of information seeking behavior by military instructors with the learning outcomes of transportation briefing of the Indonesian Army in Cimahi. This study used the correlational research method with the Spearman rank statistical test; study results showed: 1) a positive relationship between the information seeking behavior of the initiation phase and learning outcomes of transportation briefing; 2) a positive relationship between the information seeking behavior of the selection phase and the learning outcomes of transportation briefing; 3) a positive relationship between the information retrieval behavior of the exploration stage and the learning outcomes of transportation briefing; 4) a positive relationship between the information seeking behavior of the formulation stage and the learning outcomes of transportation briefing; 5) a positive relationship between the information collection stage collection behavior and the learning outcomes of transportation briefing; and 6) a positive relationship between the information seeking behavior of the presentation stage and the learning outcomes of transportation briefing. In conclusion, there is a positive relationship between information seeking behavior by military instructors and the learning outcomes of transportation briefing.